Alkenyl Boronates: Synthesis and Applications. Issue 3 (16th January 2019) - Carreras, Javier; Caballero, Ana; Pérez, Pedro J.
Abstract: Organoboron compounds have become one of the most versatile building blocks in organic synthesis owing to their accessible and efficient conversion into many different functional groups. In particular, alkenyl boronates have received a great deal of attention as very reactive substrates in Suzuki–Miyaura cross‐coupling reactions. Accordingly, efforts towards the development of efficient methods to prepare this type of compound are ongoing. In this contribution, the progress in the search for synthetic routes for alkenyl boronates and their use in a variety of organic transformations is accounted. Abstract : Middleman : Alkenyl boronates are useful intermediates to produce versatile compounds that can be further derivatized. Multiple strategies (see figure) have been employed for their synthesis. This Minireview contains the main preparation methodologies and synthetic applications of alkenyl boronates.